2014
DOI: 10.1016/j.bpj.2014.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Connexin45 Carboxyl-Terminal Domain Structure and Interactions with Molecular Partners

Abstract: Mechanisms underlying the initiation and persistence of lethal cardiac rhythms are of significant clinical and scientific interests. Gap junctions are principally involved in forming the electrical connections between myocytes, and changes in distribution, density, and properties are consistent characteristics in arrhythmic heart disease. Therefore, understanding the structure and function of gap junctions during normal and abnormal impulse propagation are essential in the control of arrhythmias. For example, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 78 publications
1
30
0
Order By: Relevance
“…Cx45CT dimerization was initially identified through the use of a recombinantly expressed soluble peptide in vitro [24]. We posited that regulatory and structural features of the isolated CT peptides would be recapitulated in cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cx45CT dimerization was initially identified through the use of a recombinantly expressed soluble peptide in vitro [24]. We posited that regulatory and structural features of the isolated CT peptides would be recapitulated in cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work from our laboratory identified high affinity dimerization ( K D ~100 nM) of soluble Cx45CT domains mediated by 6 hydrophobic residues aligned on one face of an α-helical region (A333-N361) [24, 25]. When each hydrophobic residue was replaced by glutamic acid (L335E, L338E, I324E, L349E, I353E, Y356E; construct named Cx45CT-6E; Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UBA domain of CIP75 (M549-S596) [26], Cx32CT (C217-C283) [33], Cx37CT (C233-V333) [34], Cx40CT (S251-V355) [10], Cx43CT (S255-I382) [35], Cx45CT (K265-I396) [13] and the Cx45CT dimerization domain (A333-N361) [12] were expressed and purified as previously described. For the UBA and Cx32CT domains, site-directed mutagenesis was performed to change the linker amino acid Leu3 to Trp in order to more precisely determine the protein concentration; using circular dichroism and NMR, no change in structure was observed in either of these constructs (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…They found that multiple regulatory partners bound with an intrinsically disordered region in the C-terminal, and propose that this could be a master regulatory domain. 19 Chandrababu et al used NMR to investigate the folding of the tooth enamel protein amelogenin in the presence of SDS micelles. They confirmed that the complex forms in the N-terminal region and that amelogenin increases in structure upon forming a complex with SDS.…”
mentioning
confidence: 99%